2009
DOI: 10.1002/jcb.22225
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of rat haptoglobin gene expression is coordinated by the nuclear matrix

Abstract: Using computer stress-induced duplex destabilization (SIDD) analysis and binding experiments, we identified a S/MAR element (-599/-200 bp) (Hp-S/MAR) adjacent to the cis-element (-165/-56 bp) in the rat haptoglobin gene. We examined its functional interactions with the lamins and lamin-associated proteins in the basal state and during acute-phase (AP) response-induced increased transcription. Colocalization, electrophoretic mobility shift assay (EMSA), and re-electrophoresis of nucleoprotein complexes, South-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…Subsequent identification of YY1 consensus sequences adjacent to DNA unpairing elements (UEs) [36] confirmed that, in this setting, YY1 mediates gene-nuclear matrix interactions [1]. These and other observations [42] suggest that YY1 participates in the assembly of multi-molecular gene-regulatory complexes containing PARP-1 that are modulated in a dynamic fashion by auxiliary proteins [43]. Indirect support for this comes from the observation that immediately after genotoxic treatment of HeLa cells, YY1 associates with the BRCT motif in the PARP-1 automodification domain [44] to accelerate DNA repair [45].…”
Section: Introductionmentioning
confidence: 87%
“…Subsequent identification of YY1 consensus sequences adjacent to DNA unpairing elements (UEs) [36] confirmed that, in this setting, YY1 mediates gene-nuclear matrix interactions [1]. These and other observations [42] suggest that YY1 participates in the assembly of multi-molecular gene-regulatory complexes containing PARP-1 that are modulated in a dynamic fashion by auxiliary proteins [43]. Indirect support for this comes from the observation that immediately after genotoxic treatment of HeLa cells, YY1 associates with the BRCT motif in the PARP-1 automodification domain [44] to accelerate DNA repair [45].…”
Section: Introductionmentioning
confidence: 87%